ASOSIY VOSITALARGA AMORTIZATSIYA HISOBLASH USULLARI VA TARTIBI. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The topic “Methods and procedure of depreciation calculation for fixed assets” plays a crucial role in accounting, economic theory, and financial management. Fixed assets constitute the material basis of enterprise activities and include long-term tangible assets used in the production process for several years. These assets comprise buildings and structures, machinery and equipment, transport vehicles, production tools, computer technologies, and other material resources. Over time, their value decreases due to physical wear and moral obsolescence. The gradual transfer of this value to production costs is referred to as depreciation. The primary purpose of depreciation is to determine the real value of fixed assets, accumulate financial resources for their replacement, and accurately reflect the financial results of an enterprise. In accounting practice, several methods are applied to calculate depreciation. The most widely used are the straight-line method, the declining balance method, the sum-of-years-digits method, and the units-of-production method. Each of these has its advantages and disadvantages, and the choice of method depends on the accounting policy and economic interests of the enterprise. For instance, under the straight-line method, the asset’s value is allocated evenly over its useful life. This method is simple but does not consider the fact that assets often depreciate more rapidly in the initial years. Accelerated depreciation methods, on the contrary, allocate higher amounts of depreciation in the early years, enabling companies to recover costs faster and accumulate resources for modernization. The units-of-production method, meanwhile, bases depreciation on the actual use of the asset, linking it directly to the volume of goods produced or services provided. The procedure of depreciation calculation involves determining the initial cost of the asset, its useful life, and residual value. Based on the chosen method, the depreciation amount is then calculated and recorded in the accounting books. The depreciation charge is treated as part of production costs and reduces the taxable profit, which has significant implications for both financial planning and tax accounting. The scientific and practical importance of studying this issue lies in the fact that a properly selected depreciation method ensures financial stability of the enterprise, supports investment processes, forms a correct taxation base, and contributes to improving overall economic efficiency. Therefore, enterprises today pay close attention to developing accounting policies that define optimal methods of depreciation calculation. This work analyzes in detail the theoretical approaches, depreciation methods, and the procedure of their practical application in the activity of business entities.